POLITIK IDENTITAS MELAYU MALAYSIA DAN MULTIKULTURALISME PADA FILM UPIN & IPIN : Politik Identitas dan Multikulturalisme di Film Upin Ipin - wahyudi. S, fazril wahyudi.s; Widia Ierdiana; Siti Badariah; Rindi Wulansari; Nadilla; Fitri Nurzana; Novrianti; Aditya Padini Syah (Jurnalika : Jurnal Ilmu Komunikasi, 2024)
This research aims to see how Malaysian Malay identity politics and multiculturalism appear in the film "Upin & Ipin".  The method uses a qualitative approach with content analysis as the main method. Data was obtained through in-depth observation of the narrative, characters and cultural symbols that appear in the film. The results of the research show that Malaysian Malay identity politics in the film Upin-ipin are Malay language, Malay culture, Islam, Malaysian Malay genealogy. Multiculturalism in the film Upin and Ipin is a combination of Malaysian Malay culture, Indian culture, Chinese culture, Indonesian culture. Malaysian Malay identity politics and multiculturalism exist in educational institutions in Malaysia which introduce the values ​​of tolerance and respect for cultural diversity. This film successfully promotes a message of unity and harmony through positive representations of the various Malaysian Malay ethnic identities and other ethnic cultures, such as Malays, Chinese and Indians, who live side by side in Malaysia.